An explanation for the phenotypic differences between patients bearing partial deletions of the DMD locus. - Monaco, A; Bertelson, C; Liechti-Gallati, S; Moser, H; Kunkel, L (1988)
Deletions giving rise to Duchenne muscular dystrophy (DMD) and the less severe Becker muscular dystrophy (BMD) occur in the same large gene on the short arm of the human X chromosome. We present a molecular mechanism to explain the clinical difference in severity between DMD and BMD patients who bear partial deletions of the same gene locus. The model is based on the breakpoints of intragenic deletions and their effect on the translation of triplet codons into amino acids of the protein product. Deletions identified in three DMD patients are shown to shift the translational open reading frame (ORF) of triplet codons for amino acids, and each deletion is predicted to result in a truncated, abnormal protein product. Deletions identified in three BMD patients are shown to maintain the translational ORF for amino acids and predict a shorter, lower molecular weight protein. The smaller protein product is presumed to be semifunctional and to result in a milder clinical phenotype. The same ORF mechanism is also applicable to potential 5' and 3' intron splice mutations and their effect on protein production and clinical phenotype.